Effects of Redesigned Model Eliciting Activities on Seventh Grade Students’ Mathematics Success and Students’ Views about These Activities - Karabörk, Mehmet Akif; Durmus, Soner (Universitas Malikussaleh, Aceh Utara, Indonesia, 2020)
In this study, the effects of redesigned modeling activities on the academic achievement of 7th grade students and the student’s view about these activities were investigated. We use explanatory sequential mixed method design that is one of the mixed research methodology for this investigation. The quantitative part of this research established according to semi-experimental study with pre-posttest, and qualitative part of this study execute with the case study. Quantitative data were collected with multiple choice academic achievement tests, and qualitative data were collected with study papers, observation forms, forms of student’s view, and semi-structured interviews at the end of all activities. The quantitative data were analyzed with covariance analysis. Qualitative data were analyzed with content analysis. As a result, a statistically significant difference was found in favor of the experimental group on the academic achievement which influenced by modeling activities. This difference has been influenced by the presentation of the learning environment in which the students' attitudes and beliefs towards themselves and the lessons will be positively affected, and mathematical skills will be supported to increase success.